Mechanical and Microstructural Characterization of Alkali-Activated Coconut Shell Ash Mortar - Olonade, K. A.; Bello, T. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
In this paper, potential of alkaline activation of coconut shell ash (CSA) as binder in mortar was investigated. Coconut shells were collected and calcined at temperature ranges between 500 and 900°C at interval of 100 for 30, 60 and 90 minutes to determine optimum burning condition that produces ash of higher silica content. Chemical composition of the ashes was then determined using X-ray Florescence (XRF) technique. Sodium hydroxide (NaOH) of different concentrations of 10, 12, 14 and 16 Molar (M) was used as alkaline activator, while mortar of mix ratio 1:3 was produced, while ratio of the alkali to CSA was of 0.5.  Mortar prisms of size 40 mm  40 mm  160 mm were cast and cured in an oven at a temperature of 80  for 7, 28, 56, 90 and 120 days. Thereafter, flexural and compressive strengths were determined at the end of each curing ages, following standard procedures. Scanning Electron micrographs of the hydrated mortar at 120 days were obtained using scanning electron microscopy (SEM) The results showed the oxide composition did not follow any pattern with increase in temperature but CSA produced at 800 for 1h gave the highest combined silica, alumina and ferric oxides above 70%, which is accepted as minimum value for pozzolanic materials.  Both compressive and flexural strengths of the activated mortar samples were found to increase with increase in activator concentration up to 14M and decline thereafter. At 120 days, the compressive strength was 13.9 N/mm2 while the flexural strength was 6.88 N/mm2. These values were higher than the strengths recommended by Nigerian Industrial Standard (NIS) for load bearing blocks. It was concluded that activation of CSA with NaOH could be used as binder for non-structural use. The SEM results indicated that mortar made from 14 M had structure that was densely packed compared to other mortar samples produced from other concentrations.